Comprehensive characterization of polylactide-layered double hydroxides nanocomposites as packaging materials - EROĞLU, MEHMET SAYIP (SPRINGER, 2015)
A series of biodegradable polymeric nanocomposite films based on poly(lactic acid) (PLA) and magnesium-aluminum layered double hydroxide (Mg-Al LDH) nano-particles was prepared by solution casting method. Two different Mg-Al LDH nano-fillers at Mg:Al mol ratios of 2:1 and 3:1 were synthesized by co-precipitation technique and to improve the interfacial interaction, the nanoparticles were modified by intercalating sodium dodecyl sulfate (SDS) surfactant into the LDH galleries. The PLA nanocomposite films, prepared using unmodified (Mg-Al LDH) and modified (SDS-Mg-Al LDH) nano fillers. Both XRD and TEM analyses showed an increasing dispersion and improved exfoliation of SDS-Mg-Al LDH into the PLA matrix. DMA analysis indicated that, at each composition, filler modification resulted in higher storage modulus and T-g. The composite films showed increasing oxygen barrier property up to 23.5 %, compared to PLA. The films containing 5 % of SDS-Mg-Al LDH at Mg:Al ratio of 3:1 exhibited significant increase in oxygen barrier property.
Keywords: Films; Packaging; Biodegradable; Biodegradable; Clay; POLY(LACTIC ACID); POLY(L-LACTIC ACID); NANOPARTICLES; DRUG; MG; INTERCALATION; FILMS; LDH